Kekhawatiran Masyarakat Mengenai Pembayaran Digital Sebagai Pembayaran Uang Non Tunai - Pristiyono Pristiyono (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Rumors of a national non-cash movement (GNTT) by Bank Indonesia are a form of non-cash policy implementation in Indonesia in 2030 to be a central topic researched by various academics. This study aims to determine the public perception of the level of risk posed by the use of digital money as non-cash payments in the Labuhanbatu district. The sample in this study was adopted from the total number of indicators of each variable as many as 15 indicators x 10 = 150 samples. Then the sample in this study will be taken as many as 293 based on Google form questionnaire as primary data. Data analysis in this study using Smart PLS version 3.0. The results showed that social influence and habit had a direct effect on behavior intention, while facilitating condition had no direct effect on behavior intention. Furthermore, social influence does not directly affect privacy risk, but habits and behavior intentions directly affect privacy risk. Finally, the mediated pathway coefficient shows that social influence and habit have a direct influence on behavior intention mediated through privacy risk while facilitating condition has no direct effect on behavior intention mediated through privacy risk.